Assessment of the adequacy of different Mediterranean waste biomass types for fermentative hydrogen production and the particular advantage of carob (Ceratonia siliqua L.) pulp - Ortigueira, Joana (2018)
ABSTRACT: The conversion of agro-industrial byproducts, residues and microalgae, which are representative or adapted to the Mediterranean climate, to hydrogen (H2) by C. butyricum was compared. Five biomass types were selected: brewery’s spent grain (BSG), corn cobs (CC), carob pulp (CP), Spirogyra sp. (SP) and wheat straw (WS). The biomasses were delignified and/or saccharified, except for CP which was simply submitted to aqueous extraction, to obtain fermentable solutions with 56.2e168.4 g total sugars L 1. In small-scale comparative assays, the H2 production from SP, WS, CC, BSG and CP reached 37.3, 82.6, 126.5, 175.7 and 215.8 mL (g biomass) 1, respectively. The best fermentable substrate (CP) was tested in a pH-controlled batch fermentation. The H2 production rate was 204 mL (L h) 1 and a cumulative value of 3.9 L H2 L 1 was achieved, corresponding to a H2 production yield of 70.0 mL (g biomass) 1 or 1.6 mol (mol of glucose equivalents) 1. The experimental data were used to foresight a potential energy generation of 2.4 GWh per year in Portugal, from the use of CP as substrate for H2 production.